DEVELOPING ICT-BASED LEARNING MEDIA USING CAMTASIA FOR FOURTH GRADE ELEMENTARY SCHOOL IN SD 3 BANJAR JAWA - ., Ni Luh Tresnia Widyantari; ., Kadek Sonia Piscayanti, S.Pd., M.Pd.; ., Ni Putu Astiti Pratiwi, S.Pd., M.Pd. (Universitas Pendidikan Ganesha, 2017)
The use of ICT-based learning media were rarely used to present learning material especially in the form of video made by using Camtasia Studio. The purpose of this study is to develop learning media in form of video made by using Camtasia Studio and to identify the quality of Camtasia video as learning media for fourth grade student. Thirty students of fourth grade students in SD 3 Banjar Jawa involved in implementation. Questionnaire was used to get response from the students and their English teacher. The result is significance and gets positive respond from the students and the teacher. The quality of the media assessed by three experts is excellent, good, and average. It suggested for the teachers to involve this media in learning process. It also suggested to the next researcher to conduct the related study in depth.Kata Kunci : Camtasia Studio, media for learning, young learner Penggunaan media pembelajaran berbasis ICT jarang digunakan dalam menyampaikan materi pembelajaran khususnya media dalam bentuk video yang dibuat menggunakan aplikasi Camtasia Studio. Penelitian ini bertijuan untuk mengembangkan media pembelajaran dalam bentuk video yang dibuat menggunakan Camtasia Studio dan untuk mengidentifikasi kualitas dari video tersebut sebagai media pembelajaran.untuk siswa kelas empat. Tiga puluh siswa dari kelas empat di SD 3 Banajr Jawa terlibat dalam proses implementasi. kuisioner digunakan untuk mendapatkan tanggapan dari siswa dan guru bahasa Inggris, Hasil dari penelitian ini signifikan dan mendapat tanggapan positif dari para siswa dan guru. Kualitas dari media tersbut yang dinilai oleh tiga ahli dinilai semua sangat baik, baik, dan rata-rata. Disarankan kepada para guru untuk melibatkan media daam proses belajar. Hal ini pula disarankan pula untuk peneliti lainnya untuk melakukan penelitian sejenis lebih dalam lagi.keyword : Camtasia Studio, media pembelajaran, pelajar muda